IMPACTO DA CONDIÇÃO BUCAL NA QUALIDADE DE VIDA DE PACIENTES PARCIAL E TOTALMENTE EDÊNTULOS DA UNIVERSIDADE ESTADUAL DE - Schreiner, Fabiane (2012)
Effects of alterations related to edentulism not necessarily represent changes in perception of oral health, being a matter point the exploration of the psychosocial and psychological changes for the better known of their long-term effects. Objective:The purpose of this exploratory study was to evaluate the impact of oral and prosthetic conditions on the quality of life of partially and fully edentulous patients from State University of Ponta Grossa. Method: A total of 90 individuals, 59 partially and 31 fully edentulous, were included in the study, and their socioeconomic, oral and prosthetic conditions were evaluated and compared to OHIP-14 questionnaire.The statistical data included the exploration of the psychometric properties of OHIP- 14, the bivariate analysis by Student's t test and Pearson correlation and the multivariate linear regression. Results: Sample was predominantly female and mean age presented was 52 years, ranging from 26 to 84 years. OHIP-14 mean for partially and fully edentulous was, respectively, 20.24 and 16.90; the difference was not significant (p=0.97). Items gender, education level, index of TMD and length of edentulism were associated with worse scores, whereas gender, educational level,mucosal injury and TMD index were associated with greater impact. Conclusion:After controlling the type of edentulism, both sociodemographic factors, and oral and prosthetic factors influenced the oral health related quality of life (OHRQoL). The questions with less interference in the scores were those that assessed the most severe impact, showing a high degree of adaptation to oral problems for thispopulation.